TEKNIK PENDETEKSIAN ZONA MATA AIR PANAS GEOTERMAL MENGGUNAKAN CITRA SATELIT MULTISENSOR DAN OBSERVASI LAPANGAN - Lazuardy Fajar Pratama Sulaeman; Asep Saepuloh; Permana Adhitya Lano (Fakultas Ilmu dan Teknologi Kebumian (FITB), Institut Teknologi Bandung (ITB), 2019)
Geothermal exploration activities in a very large area require a lot of time and manpower. A mapping technique can be used to minimize time and manpower at field by optimizing the use of remote sensing technology. This paper is aimed to identify the availability of geothermal hot springs zones using multisensory images from Landsat-8 Advanced Land Imager (OLI), Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) Thermal Infrared Radiometer (TIR), and Synthetic Aperture Radar (SAR) of Sentinel-1. The imagery data were prepared and used according to their respective uses, and then they will be verified by field geological data including location of hot springs and geological structures. Baolan Subdistrict and Galang Subdistrict, Tolitoli District, Central Sulawesi Province was selected as study area to obtain the effectiveness of multisensory technique under thick vegetation cover and limited access. The geological mapping area was focused in the south of Tolitoli City with coverage area about 50 km2. Surface thermal anomaly detection was performed using ASTER TIR by calculating the Land Surface Temperature (LST) and combined with wetness detection using Landsat-8 OLI. In addition, the Sentinel-1 images were used to detect lineament related to geological structures on the surface served as fluid path flows from sub-surface to surface. Ground truthing was performed by mapping hot springs at field and served as verification to the remote sensing results. Then, geological interpretation of geothermal system availability under the study area was performed. The multisensory image analyses verified by field mapping of the hot springs zone showed high effectivity to localize the possible area for surface manifestations. Meanwhile, the lineament related to geological structures based on Sentinel-1 image detected successfully a sinistral strike slip and sinistral normal faults. Accordingly, the geothermal manifestation in the study area was a discharge zone presented by the existence of hot springs and strike-slip faults acted as fractures permeability